Pengaruh Brand Image terhadap Loyalitas Pelanggan yang Dimediasi oleh Kepuasan Konsumen Produk Luwak White Coffee Mahasiswa/I di Kota Cimahi - Prastesiya, Lensi Lamuda; Sigarlaki, Faizal Fardhani (J-MAS (Jurnal Manajemen dan Sains), 2024)
In 2023, instant coffee sales in Indonesia will reach 234 million liters, an increase of 4% compared to the previous year of 225 million liters. Therefore, coffee producers are always innovative to provide products with excellent taste and quality. However, sales of Luwak White Coffee in the 2021-2023 period experienced an average decline of -2.83% from the previous year. The influence of brand image on consumer loyalty is measured through the experiences of Luwak White Coffee students in Cimahi City. This research uses quantitative methods with descriptive analysis. The population studied were students being studied in Cimahi City, with a sample size of around 90 respondents selected using the purposive method. The data analysis techniques you mentioned, namely simple regression and Sobel test, are generally used to test relationships between variables in the context of statistical analysis using SPSS version 26. The results show that brand image influences consumer satisfaction, customer loyalty and consumer satisfaction significantly, and consumer satisfaction plays a role in balancing the influence of brand image on customer loyalty.